UNAMENDABLE CLAUSES IN CONSTITUTIONAL DYNAMICS: A COMPARATIVE STUDY BETWEEN INDONESIA, FRANCE, AND GERMANY - Istikhomah, Istikhomah; Febriawanti, Dinta (TANJUNGPURA LAW JOURNAL, 2026)
Abstract Unamendable provisions, or eternity clauses, have been extensively studied in comparative constitutional law, predominantly through the German model. However, existing scholarship largely focuses on consolidated democracies and assumes that textual entrenchment ensures effective constitutional constraint. This leaves a research gap regarding how unamendability operates in transitional constitutional systems. This article offers a functional comparison of unamendable provisions in Indonesia, Germany, and France by analysing their source (textual or judicial), scope of protection, and enforcement mechanisms. The Indonesian case provides a distinctive contribution by revealing a disconnect between explicit textual unamendability under Article 37(5) of the 1945 Constitution and the absence of a judicial doctrine of unconstitutional constitutional amendment. Moreover, the constitutional status of Pancasila illustrates a critical distinction between legal and political unamendability. The study’s originality lies in reconceptualising unamendability as an institutional practice rather than a purely textual safeguard, demonstrating that its effectiveness depends on judicial enforcement and constitutional culture rather than formal entrenchment alone. Abstrak Ketentuan yang tidak dapat diubah telah banyak dikaji dalam hukum tata negara perbandingan, terutama melalui model Jerman. Namun, kajian yang ada cenderung berfokus pada demokrasi yang telah terkonsolidasi dan mengasumsikan bahwa penguncian tekstual secara otomatis menghasilkan pembatasan konstitusional yang efektif. Hal ini menimbulkan kesenjangan penelitian mengenai unamendability dalam konteks demokrasi transisional. Artikel ini membandingkan Indonesia, Jerman, dan Prancis melalui pendekatan fungsional dengan menelaah sumber unamendability, ruang lingkup perlindungan, dan mekanisme penegakannya. Konteks Indonesia menawarkan kontribusi unik dengan menunjukkan ketegangan antara unamendability tekstual Pasal 37 ayat (5) UUD 1945 dan ketiadaan doktrin unconstitutional constitutional amendment. Selain itu, Pancasila memperlihatkan perbedaan penting antara unamendability yang bersifat hukum dan politik. Kebaruan penelitian ini terletak pada pemahaman unamendability sebagai praktik institusional, bukan sekadar teknik perumusan konstitusi.